2023
DOI: 10.1002/jor.25594
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1 mediates TGF‐β1‐induced myofibroblast activation in tenocytes via mTOR signaling

Abstract: Transforming growth factor‐beta (TGF‐β1) induces plasminogen activator inhibitor 1 (PAI‐1) to effect fibrotic pathologies in several organs including tendon. Recent data implicated PAI‐1 with inhibition of phosphatase and tensin homolog (PTEN) suggesting that PAI‐1‐induced adhesions involves phosphoinositide 3‐kinase/protein kinase B/mammalian target of rapamycin (mTOR) signaling. Ergo, we investigated effects of TGF‐β1, PAI‐1, and mTOR signaling crosstalk on myofibroblast activation, senescence, and prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, in ex vivo lung tissue cultures, E4 induced MMP-1 activity and reduced collagen I, fibronectin, and PAI-1. Indeed, previous studies also indicated the roles of uPAR in attenuating myofibroblast functions, and these included proliferation, recruitment, and the subsequent progression of renal fibrosis by regulating extracellular signal-regulated kinase (ERK) signaling and reducing the extracellular accumulation of PAI-1 [ 36 ], which are also well-documented downstream targets of TGF-β1 signaling [ 11 , 37 , 38 ].…”
Section: Direct Targeting Of Myofibroblast Pathways With Peptidesmentioning
confidence: 99%
“…Furthermore, in ex vivo lung tissue cultures, E4 induced MMP-1 activity and reduced collagen I, fibronectin, and PAI-1. Indeed, previous studies also indicated the roles of uPAR in attenuating myofibroblast functions, and these included proliferation, recruitment, and the subsequent progression of renal fibrosis by regulating extracellular signal-regulated kinase (ERK) signaling and reducing the extracellular accumulation of PAI-1 [ 36 ], which are also well-documented downstream targets of TGF-β1 signaling [ 11 , 37 , 38 ].…”
Section: Direct Targeting Of Myofibroblast Pathways With Peptidesmentioning
confidence: 99%
“…The available data further suggest, moreover, that PAI-1 is a key factor in the TGF-β1driven transformation of fibroblasts to a myofibroblastic phenotype. Indeed, flexor tenocyte myofibroblast differentiation in response to TGF-β1 is significantly attenuated in SERPINE1deficient mice [112], and incubation with SK-216, a pharmacologic inhibitor of PAI-1 activity, effectively blunts the TGF-β1-induced transition of MRC-5 fibroblasts to myofibroblasts as well as the epithelial-to-mesenchymal conversion in TGF-β1-treated A549 lung epithelial cells [113]. PAI-1 binding to urokinase also induces corneal myofibroblast differentiation on a vitronectin substrate [114], while the treatment of dorsal skin wounds in FVB/NJ mice with the small molecule PAI-1 antagonist Tiplaxtinin dramatically reduced wound closure and re-epithelialization [115].…”
Section: Signaling Pathways Involved In Cca Desmoplasiamentioning
confidence: 99%
“…They initially appear in the proliferative phase to synthesize and contract the ECM to close gaps within injured tendons ( 76 ). However, the persistence of myofibroblasts is recognized as a putative driver of fibrovascular scar healing in the tendon tissue due to exuberant and sustained ECM production ( 77 ). In the flexor tendon healing, they also lead to tendon adhesions between the injured site and the surrounding tissue, preventing tendon gliding ( 78 ).…”
Section: The Mechanisms Of Nf-κb In Tendon Fibrotic Scar Healing Adhe...mentioning
confidence: 99%